A frequency-domain video transcoder for dynamic bit-rate reduction of MPEG-2 bit streams - Assuncao, P.A.A.; Ghanbari, M. (IEEE transactions on circuits and systems for video technology, 1998)
Many of the forthcoming video services and multimedia applications are expected to use preencoded video for storage and transmission. Video transcoding is intended to provide transmission flexibility to preencoded bit streams by dynamically adjusting the bit rate of these bit streams according to new bandwidth constraints that were unknown at the time of encoding. In this paper, we propose a drift-free MPEG-2 video transcoder, working entirely in the frequency domain. The various modes of motion compensation (MC) defined in MPEG-2 are implemented in the discrete cosine transform (DCT) domain at reduced computational complexity. By using approximate matrices to compute the MC-DCT blocks, we show that computational complexity can be reduced by 81% compared with the pixel domain approach. Moreover, by using a Lagrangian rate-distortion optimization for bit reallocation, we show that optimal transcoding of high-quality bit streams can produce better picture quality than that obtained by directly encoding the uncompressed video at the same bit rates using a nonoptimized Test Model 5 (TM5) encoder.